2008
DOI: 10.1089/tea.2007.0143
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Primary Hepatocyte Culture in Synthetic Self-Assembling Peptide Hydrogel

Abstract: Drug metabolism studies and liver tissue engineering necessitate stable hepatocyte cultures that express liver functions for a minimum of 4 days to 3 weeks. Current techniques, using different biomaterials and geometries, that maintain hepatocellular function in vitro exhibit a low cell density and functional capacity per unit volume. Herein we investigated a well-defined synthetic peptide that can self-assemble into threedimensional interweaving nanofiber scaffolds to form a hydrogel, PuraMatrix, as a substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(92 citation statements)
references
References 25 publications
3
88
1
Order By: Relevance
“…8 Moreover, these peptides have the motif arginine-alanineaspartic acid (RAD), which is similar to the ubiquitous integrin receptor-binding site arginine-glycine-aspartic acid (RGD), which has been studied in the context of cell attachment. 8,11,24 At present, several clinical trials of cell therapies using PuraMatrix have been reported for cartilage, 25,26 myocardial, 27 neural, [28][29][30][31] and hepatic 32,33 regeneration, indicating the potential usefulness of PuraMatrix.…”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, these peptides have the motif arginine-alanineaspartic acid (RAD), which is similar to the ubiquitous integrin receptor-binding site arginine-glycine-aspartic acid (RGD), which has been studied in the context of cell attachment. 8,11,24 At present, several clinical trials of cell therapies using PuraMatrix have been reported for cartilage, 25,26 myocardial, 27 neural, [28][29][30][31] and hepatic 32,33 regeneration, indicating the potential usefulness of PuraMatrix.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, cells are mixed with precursors in the solution phase then exposed to a change in pH, temperature, or ionic concentration to induce a gel phase transition. Common triggers include temperature sweeps from 4 to 37°C for collagen (12) and Matrigel (13), pH shifts from Ϸ2.5 to 7.4 for PuraMatrix (13) and leucine-zipper systems (5), and cation concentration increases from 20 to 200 mM for alginate (12,14) and peptide amphiphiles (8).…”
mentioning
confidence: 99%
“…Examples of the sophisticated models that, for various purposes, have been obtained from primary hepatocytes, are those generated by using bio-degradable nano-structured substrates (Kim et al, 1998), heat-sensitive polymers (Ohashi et al, 2007), various 3D matrices (Fiegel et al, 2008;ZQ. Feng et al, 2010;Ghaedi et al, 2012), or synthetic self-assembling hydrogels (Wang et al, 2008).…”
Section: Three-dimensional Liver-derived In Vitro Systems: Tissue Engmentioning
confidence: 99%